Antioxidant and Anti-Inflammatory Activities of Safflower (Carthamus tinctorius L.) Honey Extract - Li-Ping Sun; Feng-Feng Shi; Wen-Wen Zhang; Zhi-Hao Zhang; Kai Wang (Foods, 2020)
Safflower honey is a unique type of monofloral honey collected from the nectar of Carthamus tinctorius L. in the Apis mellifera colonies of northwestern China. Scant information is available regarding its chemical composition and biological activities. Here, for the first time, we investigated this honey’s chemical composition and evaluated its in vitro antioxidant and anti-inflammatory activities. Basic physicochemical parameters of the safflower honey samples in comparison to established quality standards suggested that safflower honeys presented a good level of quality. The in vitro antioxidant tests showed that extract from Carthamus tinctorius L. honey (ECH) effectively scavenged DPPH and ABTS+ free radicals. In lipopolysaccharides (LPS) activated murine macrophages inflammatory model, ECH treatment to the cells inhibited the release of nitric oxide and down-regulated the expressions of inflammatory-relating genes (iNOS, IL-1β, TNF-α and MCP-1). The expressions of the antioxidant genes TXNRD, HO-1, and NQO-1, were significantly boosted in a concentration-dependent manner. ECH decreased the phosphorylation of IκBα and inhibited the nuclear entry of the NF-κB-p65 protein, in LPS-stimulated Raw 264.7 cells, accompany with the increased expressions of Nrf-2 and HO-1, suggesting that ECH achieved the anti-inflammatory effects by inhibiting NF-κB signal transduction and boosting the antioxidant system via activating Nrf-2/HO-1 signaling. These results, taken together, indicated that safflower honey has great potential into developing as a high-quality agriproduct.